BENDING WITHOUT BREAKING: STRUCTURAL REALISM AND ASEAN’S STRATEGIC HEDGING IN THE ACFTA 3.0 UPGRADE - Ilham Dary Athallah; Hayara Khairia; Tsabita Husna; Nadine Rizqi Auliya; Fatikhatur Rizqiah (AL-BALAD : Jurnal Hukum Tata Negara dan Politik Islam, 2025)
This paper examines ASEAN’s strategic behavior in upgrading the ASEAN–China Free Trade Area (ACFTA) to “Version 3.0” in 2025 through the lens of structural realism and its auxiliary concepts of balancing, bandwagoning, and hedging. The ACFTA 3.0 Upgrade, signed in October 2025, deepens economic integration between a bloc of smaller Southeast Asian states and regional great power China – a counterintuitive development from a realist perspective given stark power asymmetry. The central question is why ASEAN member states agreed to upgrade the ACFTA to version 3.0 despite structural power asymmetry with China, and through what strategic mechanisms they managed the attendant risks to autonomy. A qualitative case study methodology is employed, analyzing treaty texts, official statements, trade and investment data, and diplomatic actions. The findings reveal that ASEAN approach to ACFTA 3.0 reflects a hedging strategy combining selective economic bandwagoning with China and concurrent diversification through parallel partnerships to preserve long-term strategic autonomy. Evidence of growing dependence – such as surging ASEAN–China trade to alongside a widening trade deficit favoring China, coexists with indicators of soft balancing, including efforts to secure safeguards in the agreement and diversified strategic alignments by certain member states. The discussion interprets these findings in light of structural realist expectations. It argues that ASEAN’s collective behavior, though seemingly at odds with realism’s prediction of balancing, can be explained by the constraints faced by weaker states in an anarchic (Waltz 1979,88) order: when direct balancing is unviable, states will bandwagon or hedge to protect their interestthe. The paper concludes that ASEAN’s upgrade of ACFTA is best understood as a hedging move under power asymmetry: a rational strategy to enhance prosperity and bind a rising China into cooperation, albeit at the cost of growing economic dependence that could limit ASEAN’s long-term strategic autonomy.